Detection of fungi by conventional methods and semi-nested PCR in patients with presumed fungal keratitis - Iman Haghani; Fatemeh Amirinia; Kiumars Nowroozpoor Dailami; Tahereh Shokohi (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Fungal keratitis is a suppurative, ulcerative, and sight-threatening infection of the cornea that sometimes leads to blindness. The aims of this study were: recuperating facilities for laboratory diagnosis, determining the causative microorganisms, and comparing conventional laboratory diagnostic tools and semi-nested PCR. Materials and Methods: Sampling was conducted in patients with suspected fungal keratitis. Two corneal scrapings specimens, one for direct smear and culture and the other for semi- nested PCR were obtained. Results: Of the 40 expected cases of mycotic keratitis, calcofluor white staining showed positivity in 25%, culture in 17.5%, KOH in 10%, and semi-nested PCR in 27.5%. The sensitivities of semi-nested PCR, KOH, and CFW were 57.1%, 28.5%, and 42% while the specificities were 78.7%, 94%, and 78.7%, respectively. The time taken for PCR assay was 4 to 8 hours, whereas positive fungal cultures took at least 5 to 7 days. Conclusion: Due to the increasing incidence of fungal infections in people with weakened immune systems, uninformed using of topical corticosteroids and improper use of contact lens, fast diagnosis and accurate treatment of keratomycosis seems to be essential. Therefore, according to the current study, molecular methods can detect mycotic keratitis early and correctly leading to appropriate treatment.